Effect of an educational intervention package on knowledge, perception and behavioral intention for breast cancer screening among adolescent students of Kathmandu Metropolitan City - Bhattarai, Preeti; Kafle, Bharat; Bhattarai, Pratik; Shrestha, Aman; Poudyal, Amod Kumar (Journal of Karnali Academy of Health Sciences, 2024)
Background: Breast cancer is the most common cancer among women worldwide and is the second most common in Nepal. This study assessed the effect of an educational intervention package on knowledge, perception, and behavioral intention for breast cancer screening among adolescent students of Kathmandu Metropolitan City. Methods: A pretest -posttest control group study design was used. Each intervention and control groups included 159 participants, selected from two randomly chosen public secondary schools. Both groups completed self administered pretest-posttest questionnaires. Educational intervention was given to the intervention group. Data was entered in EpiData 3.1 and analysed by using IBM SPSS 16 version. Wilcoxon Signed Rank test compared the difference in pretest-posttest scores within groups, and the Mann-Whitney U tested the difference between the control and the intervention groups. Results: In pretest-posttest comparisons, the intervention group showed an increase in the percentage of participants scoring at least the median value across knowledge (change: 18.0%, p<0.001), overall perception (change: 20.8%, p <0.001), and behavioral intention (change: 56.6%, p<0.001). There was significant increase in knowledge, perception, and behavioral intention among the intervention group compared to the control group (p<0.05). Conclusion: The educational intervention package showed a notable effect in increasing adolescent students’ intention to get screened for breast cancer. This study emphasizes the need to incorporate breast cancer screening programs into school level curricula. In addition, this encourages adolescents to take a proactive stance when it comes to health consciousness.